(untitled) (London Journal of Research In Management & Business, 2025)
This article focuses on the touristic stereoscopic images present in the photographs collection of Brazils Emperor, D. Pedro II. Firstly, we will present the concept of "stereoscopic tour" and its diffusion in nineteenth-century modernity. From the constitution of the Emperor’s Collection, we will address its importance for the construction of an ideal of nation and for the emperor’s image himself as a "monarch-citzen". Finally, we discuss the role occupied by tourist stereoscopies in the collection, their uses and functions and the possible relationships between them and the trips undertaken by this tropical monarch.